The effect of cooling condition on the microstructure and properties of Al-4.4Cu-0.8Si-0.5Mg powder compacts - Khairul Nazri Taha (Universiti Malaysia Perlis, 2008)
The aim of this research is to study the effect of cooling condition on microstructure and properties of Al alloy. Powder compacts from a premixed commercial aluminium powder Al-4.4Cu-0.8Si-0.5Mg (wt %) grade have been sintered and passed through a different cooling method process. The mentioned stated of cooling process is normalizing and quenching. Based on the different types of cooling method it’s bring to the different on microstructure and mechanical properties for each of the sample. These mechanical properties are obtained by series of test mention above which is hardness test, density and porosity measurement, microstructure observation. The samples of powder compacts have been investigated by Microhardness Vickers machine for hardness test, Scanning Electron Microscope (SEM) for microstructure analysis and density balance for density and porosity measurement. Conclusions made through this project are hundred percent based on the result and discussion made.